2014
DOI: 10.1038/nphys3078
|View full text |Cite
|
Sign up to set email alerts
|

Scaling macroscopic aquatic locomotion

Abstract: Inertial aquatic swimmers that use undulatory gaits range in length L from a few millimetres to 30 metres, across a wide array of biological taxa. Using elementary hydrodynamic arguments, we uncover a unifying mechanistic principle characterizing their locomotion by deriving a scaling relation that links swimming speed U to body kinematics (tail beat amplitude A and frequency ω) and fluid properties (kinematic viscosity ν). This principle can be simply couched as the power law Re ∼ Sw α , where Re = UL/ν 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
280
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(320 citation statements)
references
References 26 publications
(20 reference statements)
35
280
4
1
Order By: Relevance
“…2E we show that U=L = α a Ω=2π, where α a approaches the experimental value of ∼ 0:75 when the scaled amplitude of the swimmer approaches a = 4:75 (Supporting Information). Analyzing our results in terms of the Strouhal number St = λω=ð2πuÞ, which mixes the input variables λ; ω and output variable u, we find that St associated with the velocity peaks is also in agreement with experimental observations (25,36) that show that 0:1 K St K 0:4 (Supporting Information).…”
Section: Analysis Andsupporting
confidence: 84%
See 2 more Smart Citations
“…2E we show that U=L = α a Ω=2π, where α a approaches the experimental value of ∼ 0:75 when the scaled amplitude of the swimmer approaches a = 4:75 (Supporting Information). Analyzing our results in terms of the Strouhal number St = λω=ð2πuÞ, which mixes the input variables λ; ω and output variable u, we find that St associated with the velocity peaks is also in agreement with experimental observations (25,36) that show that 0:1 K St K 0:4 (Supporting Information).…”
Section: Analysis Andsupporting
confidence: 84%
“…We start by showing that our theory is consistent with a recent comparative analysis of macroscopic swimming (25). In the laminar regime, balancing the propulsive term with the viscous drag in Eq.…”
Section: Analysis Andsupporting
confidence: 80%
See 1 more Smart Citation
“…This equation is adapted and simplified from (Kopman et al 2015) for the case of straight swimming, neglecting the angle of attack and the body dynamic motions of yaw and sway. This equation should be considered as a first approximation of the tail beat undulation of live animals (Gazzola et al 2014). Therein, it was shown that a simple, monochromatic function could be used to accurately explain the dependence of swimming speed on tail beat frequency and amplitude, across a wide range of aquatic species from fish to mammals.…”
Section: Swimming Experimentsmentioning
confidence: 99%
“…For instance, through its passive shape reconfiguration in the flow, a tree leaf can achieve substantial and beneficial drag reduction [1,2]. Similarly, a fish can exploit energy from the surrounding vortex street and achieve cost savings by undulating its body [3][4][5]. The famous experiment conducted by Liao et al revealed that a trout can decrease muscle activity by synchronizing its kinematics to incoming vortices appropriately [6].…”
Section: Introductionmentioning
confidence: 99%